2014
DOI: 10.1128/mcb.00206-14
|View full text |Cite
|
Sign up to set email alerts
|

Regulated Proteolysis of NOTCH2 and NOTCH3 Receptors by ADAM10 and Presenilins

Abstract: cIn mammals, there are four NOTCH receptors and five Delta-Jagged-type ligands regulating many aspects of embryonic development and adult tissue homeostasis. NOTCH proteins are type I transmembrane receptors that interact with ligands on adjacent cells and are activated by regulated intramembrane proteolysis (RIP). The activation mechanism of NOTCH1 receptors upon ligand binding is well understood and requires cleavage by ADAM10 metalloproteases prior to intramembranous cleavage by ␥-secretase. How the other h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
73
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 61 publications
(76 reference statements)
4
73
0
Order By: Relevance
“…The HD is cleaved during normal receptor maturation by a furin-like protease at a site called S1 (Logeat et al, 1998), but the NRR is resistant to further proteolysis in the absence of ligand (Gordon et al, 2007; Sanchez-Irizarry et al, 2004). Ligand stimulation induces receptor sensitivity to metalloprotease cleavage at a site called S2 (Brou et al, 2000; Groot et al, 2014; Mumm et al, 2000), which lies near the C-terminal end of the HD (Figure 1A). After metalloprotease cleavage, the truncated receptor, called NEXT, is primed for intramembrane cleavage at site S3 and additional sites by gamma secretase, which releases the intracellular part of Notch (NICD) from the membrane.…”
mentioning
confidence: 99%
“…The HD is cleaved during normal receptor maturation by a furin-like protease at a site called S1 (Logeat et al, 1998), but the NRR is resistant to further proteolysis in the absence of ligand (Gordon et al, 2007; Sanchez-Irizarry et al, 2004). Ligand stimulation induces receptor sensitivity to metalloprotease cleavage at a site called S2 (Brou et al, 2000; Groot et al, 2014; Mumm et al, 2000), which lies near the C-terminal end of the HD (Figure 1A). After metalloprotease cleavage, the truncated receptor, called NEXT, is primed for intramembrane cleavage at site S3 and additional sites by gamma secretase, which releases the intracellular part of Notch (NICD) from the membrane.…”
mentioning
confidence: 99%
“…We recently demonstrated that ligand induced proteolysis of NOTCH proteins is similar and all require the Adam10 protease and presenilin1/2-dependent ␥-secretase activity (12). The mechanism by which leukemia associated NOTCH1 HD mutations contribute to ligand independency in T-ALL has also been amply studied and involves destabilization of the NRR (6,18).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmids and Transfections-Full-length human NOTCH1 and NOTCH2 cDNAs used here were constructed as described previously (12). Full-length FLAG-tagged mouse Notch2 cDNA was a kind gift from Y. Hamada and was described previously (25).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations